Factors Affecting Long-Term Survival Following Pulmonary Metastasectomy of Renal Cell Carcinoma - Saricam, Murat (Urology Journal, 2020)
Purpose: Role of pulmonary metastasectomy of renal cell carcinoma (RCC) is significant considering its contribution to survival rates. The aim of this study is to present the prognostic factors affecting the surgical outcomes and long-term survival. Materials and Methods: Forty-eight patients who had undergone pulmonary metastasectomy of RCC between 2000 and 2018 were analyzed in terms of gender, age, subtypes and pathological T stages of RCC, side and size of pulmonary metastases, disease-free interval (DFI) and type of lung resections in order to reveal the prognostic factors from the stand point of selecting suitable patients for lung metastasectomy. Results: Overall survival was 56.2 ±21.7 months. Survival time was less than 3 years for 7 (14.6%) , between 3 and 5 years for 11 (22.9%) and more than 5 years for 30 (62.5%) patients. Young age, female gender, unilateral pulmonary lesions, longer DFI, lung metastases limited in number and volume were statistically significant for better survival rates (P <.05) whereas subtypes and pathological stage of the primary tumor or the type of pulmonary metastasectomy did not act on the outcomes (P >.05). Conclusion: The most distinctive factor affecting the surgical outcomes is the complete resection of lung metastases rather than the extent of the surgery. This study clearly states that patients aged under 50 years with unilateral lung metastases counting less than 3 and measuring smaller than 4 cm3 and also DFI lasting longer than 32 months benefit from pulmonary metastasectomy of RCC.